Effect of Moisture on the Strength of Stabilized Clay with Lime-Rice Husk Ash and Fibre Against Wetting-Drying Cycle - Muntohar, Agus Setyo (International Journal of Integrated Engineering, 2019)
This paper presents the stabilisation of clay soil using lime-rice husk ash with polypropylene fibre reinforcement. Environmental effect of wetting and drying cycles was considered as a caused factor for decreasing the performance of the road pavement. Three moisture content regimes, i.e. optimum-dry moisture content (ODM), optimum moisture content (OMC), and optimum-wet moisture content (OWM), are studied as initial condition of the compacted soil. The soil was mixed with 17% lime and 17% rice husk ash and reinforced with 0.4% fibres. This research investigates the effect of moisture content on the strength behaviour of the stabilized soil with lime-RHA and fibres reinforcement under wetting-drying cycles. The specimen experienced up to four W-D cycles. In general, the unconfined compressive strength (qu) increases up to three W-D cycles and thereafter decreases. Wetting-drying cycles reduces qu after fourth cycles and increases the brittleness of the stabilised soil. This study concludes that the stabilised soil with lime-RHA and fibres should be compacted at the optimum wet moisture content to meet the requirement as unbound layer for pavement structure.